ANALISIS KELAYAKAN FINANSIAL METE RAKYAT DI KABIIPATEN LOMBOK BARAT NINA TENGGARA BARAT - Patricia Ratnawati (Jurnal Manajemen FE-UB, 2013)
The Purpose of the Study was to investigate the Financial Feasibility qt Agribusiness. Farmer Cashew Agribusiness. The Research Method was surveys in West Lombok Districts.11w respondent were 96 people in West Lombok district, consisting of 74 Farmers, 14 Merchant, 6 Government Officers, 1 Banker and 1 Cashew manufacturing. They were selected by purposive random sampling. The data was collected through questionnaire, interview, and field observation. I1w Instrument was based on relevant theory, from research reports, and guide line of agriculture Department and literature review. The internal consistency of the instrument was assessed by experts. The data was Analyzed using Financial Analysis